The Relationship of Family Attachment and Resilience with Psychological Well-Being among Adolescents Experiencing Parental Divorce in Baleendah District, Bandung Regency - Delisa Astuti; Prinska Damara Sastri (International Journal of Marketing & Human Resource Research, 2026)
Parental divorce represents a significant life stressor that may disrupt adolescents’ psychological well-being. This study aims to examine the effects of family attachment and resilience on psychological well-being among adolescents experiencing parental divorce. A quantitative, cross-sectional design was employed, involving 60 adolescents aged 12–18 years from divorced families in Baleendah District, Indonesia. Data were collected using self-report scales assessing family attachment, resilience, and psychological well-being, and analyzed using multiple linear regression. The findings indicate that resilience has a positive and significant effect on adolescents’ psychological well-being, whereas family attachment does not demonstrate a significant direct effect. However, both variables jointly explain variation in psychological well-being, with resilience playing a more dominant role. These results suggest that adolescents’ internal adaptive capacities are more critical than relational factors alone in maintaining psychological well-being following parental divorce. This study contributes to the literature by integrating relational and adaptive factors within a single empirical model and highlights the importance of resilience-building interventions to support adolescents’ psychological adjustment in post-divorce family contexts